APPLICATION OF THE CONTEXTUAL TEACHING AND LEARNING (CTL) MODEL WITH THE ASSISTANCE OF TRANSPARENT MIKA MEDIA TO IMPROVE THE LEARNING OUTCOMES OF CLASS V STUDENTS OF JAYALAKSANA 3 PUBLIC ELEMENTARY SCHOOL - Nita Harrisah; Faridillah Fahmi Nurfurqon; Febby Fajar Nugraha (Kopertis Region IV Jabar and Banten, 2023)
This research is conducted by problems in the field that learning mathematics in the material of adding fractions in elementary schools only accentuates arithmetic and memorization skills which resulting in low student learning outcomes. The purpose of this study is to improve student learning outcomes through the application of the Contextual Teaching and Learning model assisted by transparent mika media. The research method used is Classroom Action Research Kemmis and Mc Taggart Models which consists of four stepÂ that is planning, implementing, observing, and reflecting. Data collection techniques were carried out by means of observation and written tests. The subjects of this study were fifth grade students at SDN 3Â Jayalaksana with a total of 16 students. The material is about the operation of adding fractions. The results showed that there was an increase in student learning outcomes in the material for fraction addition operations. In the first cycle, the average student learning outcomes were 66, in the second cycle, the average student learning outcomes were 70, and in the third cycle, the average student learning outcomes were 80 with good predicate (B). Based on these results, it can be concluded that the application of the CTL model assisted by transparent mika media can improve the learning outcomes of fifth grade students in the fraction of addition.